Growth Parameters and Carcass Quality of Broilers Fed a Corn-Soybean Diet Supplemented with Creatine Monohydrate - Stahl, C.A.; Greenwood, M.W.; Berg, E.P. (International Journal of Poultry Science, 2003)
A six-week study was conducted to determine the feed efficiency and carcass quality of broilers supplemented creatine monohydrate. Day-old (unsexed) broiler chicks (n = 288) were allotted to one of three dietary treatments (12 chicks/pen, eight replications/treatment) using a completely randomized design. The control diet (diet A) contained 0% creatine throughout the entirety of the six week study. Diet B contained 0% creatine weeks 1-3 and 0.63% creatine weeks 4-6, while diet C contained 1.05% creatine weeks 1-3 and 0.63% creatine weeks 4-6. Each diet was formulated to meet or exceeded the nutrient requirements of broilers. During week four of the experiment, the feed efficiency of chicks fed diet B was superior (P < 0.05) to that of birds fed diet A. Intramuscular pH measured at 30 min postmortem was lower (P < 0.05) in the breast meat of broilers fed diet C. Moreover, the breast meat from broilers fed diets B and C was paler (higher L*-values) than that of birds fed the control diet (P < 0.05). In conclusion, the data indicate that feed efficiency was improved from weeks three to four after a creatine loading period. However, the carcasses from broilers fed creatine exhibited a paler breast meat color and a lower breast muscle pH (diet C) when compared to diet A.